2013
DOI: 10.1190/geo2012-0528.1
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of acoustic responses on the injection of supercritical CO2 into sandstones from the Otway Basin

Abstract: Quantitative knowledge of the acoustic response of rock from an injection site on supercritical CO 2 (scCO 2 ) saturation is crucial for understanding the feasibility of time-lapse seismic monitoring of CO 2 plume migration. A suite of shaley sandstones from the injection interval of the CRC-2 well, Otway Basin, Australia is tested to reveal the effects of supercritical CO 2 injection on acoustic responses. CO 2 is first injected into dry samples, flushed out with brine and then injected again into brine-satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Several experimental studies have been performed in an attempt to understand the seismic wave characteristics in partially saturated porous media (Murphy, 1982;Knight and Nolen-Hoeksema, 1990;Gist, 1994;Cadoret et al, 1995;Geller et al, 2000;Monsen and Johnstad, 2005;Xue and Lei, 2006;Shi et al, 2007;Lebedev et al, 2009;Xue et al, 2009;Lebedev et al, 2013). In conventional displacement experiments between gas (such as air or nitrogen) and water, some experimental studies have evidenced clear hysteresis in the relationship between P-wave velocity/attenuation and fluid saturation in a drainage-imbibition cycle (Domenico, 1976;Knight and Nolen-Hoeksema, 1990;Yin et al, 1992;Cadoret et al, 1995Cadoret et al, , 1998.…”
Section: Introductionmentioning
confidence: 98%
“…Several experimental studies have been performed in an attempt to understand the seismic wave characteristics in partially saturated porous media (Murphy, 1982;Knight and Nolen-Hoeksema, 1990;Gist, 1994;Cadoret et al, 1995;Geller et al, 2000;Monsen and Johnstad, 2005;Xue and Lei, 2006;Shi et al, 2007;Lebedev et al, 2009;Xue et al, 2009;Lebedev et al, 2013). In conventional displacement experiments between gas (such as air or nitrogen) and water, some experimental studies have evidenced clear hysteresis in the relationship between P-wave velocity/attenuation and fluid saturation in a drainage-imbibition cycle (Domenico, 1976;Knight and Nolen-Hoeksema, 1990;Yin et al, 1992;Cadoret et al, 1995Cadoret et al, , 1998.…”
Section: Introductionmentioning
confidence: 98%
“…Ultrasonic measurements were performed using the experimental technique described by Lebedev et al (2013). We use V153 1MHz/.5″ transducers (Olympus Panametrics-NDT™) working in shear mode (S-transducers).…”
Section: Methodsmentioning
confidence: 99%
“…In this work we use S-transducers to emit ultrasonic pulse as it was shown that such technique allows registration not only S-wave but P-wave as well (for more details see Lebedev et al, 2013). However, source S-transducer converts transmitted electrical signal to mechanical displacement parallel to its surface.…”
Section: Aseg-pesa-aig 2016mentioning
confidence: 99%
“…All measurements are conducted under room temperature and radial and axial stresses are equal (referred to as confining pressure). The experimental procedure described in Lebedev et al (2013) is used to measure P-wave and S-wave velocities (Vp and Vs respectively). Tri-axial tests have been run by CSIRO to understand the structural and tectonic history and its relation to the diagenesis and low rank metamorphism of the rocks but the results are not reported here.…”
Section: Methodsmentioning
confidence: 99%